Microbial Extracellular Polymeric Substances (EPSs) in Ocean Systems - Decho, Alan W.; Gutierrez, Tony (Frontiers in Microbiology, 2017)
Microbial cells (i.e. bacteria, archaea, microeukaryotes) in oceans secrete a diverse array of large molecules, collectively called extracellular polymeric substances (EPS) or simply exopolymers. These secretions facilitate attachment to surfaces that lead to the formation of structured 'biofilm' communities. In open-water environments, they also lead to formation of organic colloids, and larger aggregations of cells, called ‘marine snow’. Secretion of EPS is now recognized as a fundamental microbial adaptation, occurring under many environmental conditions, and one that influences many ocean processes. This relatively recent realization has revolutionized our understanding of microbial impacts on ocean systems. EPS occur in a range of molecular sizes, conformations and physical/chemical properties, and polysaccharides, proteins, lipids and even nucleic acids are actively-secreted components. Interestingly, however, the physical ultrastructure of how individual EPS interact with each other is poorly-understood. Together, the EPS matrix molecules form a three-dimensional architecture from which cells may localize extracellular activities and conduct cooperative/ antagonistic interactions that cannot be accomplished efficiently by free-living cells. EPS alter optical signatures of sediments and seawater, and are involved in biogeomineral precipitation and the construction of microbial macrostructures, and horizontal-transfers of genetic information. In the water-column, they contribute to the formation of marine snow, transparent exopolymer particles (TEP), sea-surface microlayer biofilm, and marine oil snow (MOS). Excessive production of EPS occurs during later-stages of phytoplankton blooms as an excess metabolic byproduct and releases a carbon pool that transitions among dissolved-, colloidal-, and gel-states. Some EPS are highly-labile carbon forms, while other forms appear quite refractory to degradation. Emerging studies suggest that EPS contribute to efficient trophic-transfer of environmental contaminants, and may provide a protective refugia for pathogenic cells within marine systems; one that enhances their survival/persistence. Finally, these secretions are prominent in ‘extreme’ environments ranging from sea-ice communities to hypersaline systems to the high-temperatures/pressures of hydrothermal-vent systems. This overview summarizes some of the roles of exopolymer in oceans.